Examining The Impact Of Risk Management Strategies On Minimizing Delays And Cost overruns In Large-Scale Construction Projects - Cholakkal, Biju Basheer (My University, 2025)
Construction projects in modern days are complex due to the potential challenges that can cause budget overshoot and project delays. The study aims to identify the effect of risk management solutions to reduce delays and cost overrun issues in large-scale construction projects. According to the findings of the previous literature, labour shortage is a major concern that causes delays and defects in the building process. Workplace safety training is vital for ensuring that the project is completed by following appropriate measures. On the other hand, collaboration and communication with all the stakeholders of the project is paramount to make effective decisions which is essential to meet the outcomes of the project in a successful way. However, risk management is important for ensuring the success of the project. Monitoring the risk management procedure is imperative to identify the potential challenge that can impact the overall project outcomes. Real-time monitoring tools can be used for identifying warning signs and following preventive measures. Primary quantitative and secondary qualitative data are collected in this paper. The primary quantitative data is collected by organising a survey using Webropol. The survey link was shared with professionals from the construction industry. Total of 54 survey responses were received. Additionally, secondary data was collected from previously published academic journals and articles. Mixed data is used in the study to successfully meet the objectives of the research. According to the findings of the research paper, it is clear that effective risk management strategies are fundamental to avoid delays and cost overrun issues in construction projects. In this regard, companies need to monitor and evaluate the overall project functions in a suitable manner. Providing appropriate training to the employees associated with the project is also key for developing their skills and abilities in order to mitigate the risk. Additionally, multiple kinds of new technology can be used by the company for early detection of the possible risk in the project. A risk management framework must be included for determining the possible risks in the construction project. Moreover, this study includes effective knowledge and meaningful insights about the project management procedure. Appropriate implementation of the risk monitoring process can help all the project stakeholders enhance risk preparedness and reduce the likelihood of any disruption. As a result, better project delivery can be ensured by the construction companies. In future, the research can be done in a more effective way by including primary qualitative data. Increasing the budget and the time for the research can help to collect more qualitative data for this research. Appropriate identification of the key elements of large-scale construction projects can help to follow sustainable approaches that can develop construction companies and provide them success.
Keywords: risk management; project management; risks; construction industry; projects; construction sector; construction projects; project leadership; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Management; Strategic Project Management